2014
DOI: 10.1002/pip.2521
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spatial separation of type‐II GaSb quantum dots from the depletion region on the conversion efficiency limit of GaAs solar cells

Abstract: The purpose of this work is to look for a practical structure for application of quantum dots (QD) in solar cells in order to enhance sub-band gap photon absorption. We focuse on a stack of strain-compensated GaSb/GaAs type-II QDs. We propose a novel structure with GaSb/GaAs type-II QD absorber embedded in the p-doped region of ideal solar cell, but spatially separated from the depletion region. We developed the model and used the detailed balance principle along with Poisson and continuity equations for calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Semiconductor core/shell quantum dots (QDs) receive strong attention due to the tunability of their electronic properties, leading to many relevant nanotechnology and optoelectronic applications [1][2][3][4][5][6][7]. Both germanium and silicon are materials frequently used in the electronic industry; in addition, they show strong confinement effects in QDs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor core/shell quantum dots (QDs) receive strong attention due to the tunability of their electronic properties, leading to many relevant nanotechnology and optoelectronic applications [1][2][3][4][5][6][7]. Both germanium and silicon are materials frequently used in the electronic industry; in addition, they show strong confinement effects in QDs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We have already shown that intra-band QD absorption of longwavelength part of solar spectrum with photon energy being less than the energy band gap of QDs facilitates exciton disintegration in GaSb/GaAs type-II QD absorber [8]. Such intra-band absorption transfers photon energy to confined holes.…”
Section: Introductionmentioning
confidence: 99%
“…This process leads to generation of dark current in the depletion region of p-n-junctions. Therefore, embedding of smaller energy band gap materials like QDs into the depletion region inevitably increases the dark current generated in the p-n-junction [8]. Numerous experimental studies of QD solar cells demonstrated such increase of the dark current [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, electron-hole recombination in QDs results in additional dark current which reduces the open circuit voltage and keeps the conversion efficiency of QD solar cells below the Shockley-Queisser limit. Using a GaSb/GaAs type II QD absorber embedded in the p-doped region of an ideal solar cell but spatially separated from the depletion region is expected to lead to voltage preservation [2]. Meanwhile, improvements in voltage preservation through suppression of hole thermionic emission rates by n-type doping at the expense of reduction in short circuit current and by positioning of QD layers at the edge of the space charge region have been reported [3].…”
Section: Introductionmentioning
confidence: 99%